Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Produk Kesehatan Kulit - Zulhamdani Zulhamdani; Iswahyudi Iswahyudi; Ade Davy Wiranata (SYNERGY: Jurnal Bisnis dan Manajemen, 2024)
Increased economic growth and people's lifestyles that have experienced a lot of shifts makes the need for beauty products increase, moreover this is also accompanied by the development of various skin diseases that are increasingly being found, this is caused by many people who want to look different, increased pollution , bad lifestyle and many other causes. Society as the target consumer company gets many choices of products offered from various corporate brands. It makes people have to be more careful in buying the products offered according to their needs and illness. Noting the above description, the researcher is interested in conducting a thesis research entitled "The Effect of Marketing Mix on Purchasing Decisions of PT Qilah Prime Healthcare Skin Products in North Jakarta 1" The population in this study are consumers or potential consumers of skin health products PT Qilah Prime Healthcare region which includes 3 villages, kemayoran, pademangan and sunter kelurahan as many as 100 people. From the product quality testing of the purchase decision made the test results obtained t = 2.506 with a significance = 0.014. The results of this test, conclude that the product quality is partially positive and significant effect on purchasing decisions. That is, the higher the partial quality of the product, the higher the purchase decision. From the tests performed the test results obtained for F = 23,985 with a significance = 0,000. The results of this test, conclude that together product quality, pricing strategies, promotion methods, and distribution channels have a positive and significant effect on purchasing decisions. That is, the higher the product quality, pricing strategy, promotion methods, and distribution channels together, the higher the purchasing decision.